Tenant Satisfaction, Trust, Green Image as Mediation, and Greenwashing Perception as Mediator of the Perceived Intention to Extend or Renew Rent - Felicia Solihin; Raden Alibasya Wisnu Wardhana; Suharno Tan; Asnan Furinto; Dewi Tamara (Australasian Accounting, Business and Finance Journal, 2023)
This research aimed to observe the influence of tenant satisfaction, green awareness, and trust through green image mediation, and moderation by greenwashing perception perceived intention to extend or renew rent and studied in one of the biggest shopping malls in Jakarta. The research collected data through surveys of 229 respondents who are tenants with a minimum of one year of rent at this shopping mall. Although many research projects have shown that tenant satisfaction and tenant trust have a positive influence on tenant intention to extend or renew rent, it had yet to examine the factors of green awareness, green image, and greenwashing perception combined with tenant satisfaction and tenant trust to decide to extend or renew rent. This study found that tenant satisfaction, green awareness, green image, and greenwashing perception influence tenant intention to extend or renew rent. Tenant satisfaction directly influenced tenant intention to extend or renew rent, followed by tenant trust, but does not apply to green awareness. Mediation of green image did not influence tenant intention to extend or renew rent, and greenwashing perception as a moderator on green image negatively affects tenant intention to extend or renew rent. This research contributed not only knowledge about how company management can improve the perception of tenant intention to extend or renew rent through the variables mentioned above but also aligned strategy to Sustainable Development Goals (SDGs) in affordable clean energy, Industry-Innovation, and infrastructure, climate action, and partnerships for the goals by found the phenomenon of tenant satisfaction, green awareness, and tenant trust directly influenced green image. Ritel companies can apply the findings from this study to enhance tenant intention to extend or renew rent and be of further use for further academic research.
Keywords: Intention to Extend/Renew Rent; Tenant Satisfaction; Green Awareness; Trust; Green Image; Greenwashing Perception